The Persuasive Function of the Title as a “Movere” Tool in Journalistic Film Reviews - Topa-Bryniarska, Dominika (Respectus Philologicus, 2022)
Based on theories in pragmatics, rhetoric, argumentation and discourse analysis, the genre of “journalistic film review”, relatively little examined, has been analysed in this paper as a discourse reflecting a justified assessment. Our analysis, presented as a case study, concerns the persuasive function of the titles of 53 French and francophone film reviews. In this analysis, the act of persuasion, anchored in Perelman’s (1971) concept of argumentation, corresponds to the rhetorical structure of public discourse. For the act of persuasion, we focus on discursive and stylistic parameters related to the rhetorical principle of “movere” as the basis of the film review’s deliberative (advisory and justifying) dimension. The role of this dimension is to invite the addressee to co-create the meaning of the discourse through the process of co-schematisation, implemented with the help of emotional argumentation in the form of appraisive and affective lexemes. These stylistic devices also constitute a mechanism of persuasion typical of advertising discourse.